PENGARUH PENGGUNAAN KOSMETIK SKIN CARE TERHADAP TIMBULNYA ACNE VULGARIS PADA SISWA KECANTIKAN SMKN 6 DAN SMN 7 PADANG - Stephanie Mutiara (JURNAL PENDIDIKAN DAN KELUARGA, 2019)
Protective cosmetics are cosmetics that can protect the skin by refusing and absorbing the sun.Efforts to prevent acne can be done to avoid triggering factors as well as prevent zits such as regular life, getting enough rest, avoiding stress, maintaining emotions, avoiding dust pollution, using adequate cosmetics, and avoiding the disruption of oil glands.This study aims to determine the effect of cosmetrickin use care on the emergence of Acne Vulgaris in Beauty Students in Vocational High School 6 and 7 Vocational High School Padang.This study is an analytical study with a cross sectional approach, where researchers measure variables simultaneously and the results obtained describe the conditions that occur when the study is carried out.This research was conducted in October 2018 at SMK Negeri 6 and SMK Negeri 7 Padang.The population in this study were students majoring in Beauty at Padang N 6 Vocational School and Padang N 7 Vocational School..Sampling using Slovin formula.Data analysis techniques are using Chi Square Test analysis. The results of the analysis show that there is a significant influence between the use of cosmetic skin care in the form of cleanser(sig = 0.018), moisturizer (sig = 0.013), protector (sig = 0.008) and thinner(sig = 0.002) against the onset of student acne vulgaris